"Beyond the Prison Gate": Exploring Recognition through Photography with Former Political Prisoners in Myanmar. Issue 1 (1st January 2021) - Gaborit, Liv S.
Abstract : This article argues that imprisonment is a liminal experience and that recognition is needed to establish a new social status to enable parity of participation after one's release. The article builds on photographic action research done with four former political prisoners in Myanmar, and analyzes three of the photos from the project and the process of creating and exhibiting photos. The article shows how former prisoners experience prolonged liminality, and it argues that recognition and access to parity of participation are key to prevent such prolonged liminality and to offer redress for the injustice and misrecognition that former political prisoners experienced.